Evaluation of Yields and Grain Filling Speeds of Bread Wheat Genotypes under End-of-the-Season Drought Stress Conditions - Ahmad Shahizadeh; Rasool Asghari Zakaria; Marefat Ghasemi; Parisa Sheikhzadeh Mosaddeq (پژوهشنامه اصلاح گیاهان زراعی)
Extended abstract Background: One method for selecting high-yielding cultivars is selection based on physiological traits. Investigating the seed growth and filling process and its effect on seed weight is among the basic research in breeding programs. The speed and period of grain filling are important traits affecting grain yield in wheat, which are affected by environmental conditions. Selection based on traits such as seed filling speed and period can be a good physiological criterion for cultivar evaluation. This research aimed to evaluate the yield, speed, and period of grain-filling in bread wheat genotypes under end-of-the-season drought stress conditions and to identify superior genotypes. Methods: In this research, 18 bread wheat genotypes along with two control varieties were obtained from the Ardabil Agricultural Research Station and Natural Resources. An experiment was conducted in a completely randomized block design with three replicates in two conditions of full irrigation and drought stress at the end of the season in the Ardabil Agricultural Research Station. In the field, the genotypes were cultivated inside each plot of 4 × 3 m with a distance of 20 cm between lines and a density of 400 seeds/m2. Genotypes were cultivated in the research station in the fall of 2019. In stress conditions, irrigation was not applied from flowering to seed maturity, while irrigation was carried out three times (early flowering, mid-seed setting, and late seed setting) from flowering to physiological maturity in stress-free conditions. Grain yield traits, grain filling speed, maximum grain dry weight, length of grain filling period, and effective grain filling period were measured in this study. Results: The results of variance analysis for the evaluated traits showed a significant difference between environments and between genotypes in all evaluated traits. The genotype × environment interaction effect was also significant for all mentioned traits. The significance of the difference between genotypes indicates genetic diversity between the studied cultivars. Moreover, the significance of the interaction effect showed that the studied genotypes did not behave the same in two environments without and with stress. The seed-filling rate of all genotypes decreased under drought-stress conditions. The average seed-filling rates were 1.20 and 1.37 mg per day in the stressed and non-stressed environments, respectively. The length of the grain-filling period and the effective grain-filling period decreased with increasing the grain-filling speed. The length of the seed-filling period in the stressed environment was shorter by 2.31 days on average. The effective length and period of seed filling were directly related to the seed dry weight. The average yield of genotypes under stress conditions (594 g/m2) declined significantly compared to the non-stress environment (768 g/m2). On average, the length of the seed-filling period in the stressed environment (34.90 days) was shorter than that in the non-stressed environment (37.21 days). The greatest decrease in the effective length of seed filling was observed in genotype 5 (5.30 days). The longest seed-filling periods were recorded for genotypes 14 (41 days) and 12 (40.44 days) in stress conditions, and genotype No. 13 (43.21 days) in non-stress conditions. Genotype 3 showed the shortest seed-filling period in both stress and non-stress conditions. The correlation coefficients showed a negative and significant correlation between the speed and the effective period of seed filling in the stress (r = -0.358**) and non-stress (r = -0.404**) environments. A cluster analysis of the genotypes grouped them into three and four clusters in the stress and non-stress environments, respectively. The heat map of the distribution of genotypes grouped them into three clusters based on the traits studied in the stressful environment. Genotypes 19, 18, 3, 10, and 1 were in the first group, with a short effective seed-filling period and a higher filling speed, which was desirable due to the relatively better yield. The second group included genotypes 7, 4, 9, 17, 6, 5, and 8, with lower seed yields and short effective seed-filling periods. Finally, genotypes 13, 12, 2, 14, 11, 20, 15, and 16 were included in the third group, with lower values of speed and maximum seed weight and higher values  of effective seed-filling periods. Members of this group showed relatively good yields, which could be attributed to the length and long effective seed-filling period. Considering the importance of grain-filling processes to reach the desired grain weight, selection to increase the grain-filling speed and the effective long filling period can lead to more yields in stressful conditions. Conclusion: A significant variation in traits was observed among the studied genotypes, indicating the existence of appropriate genetic diversity in the studied plant material. End-of-season drought stress negatively affected the final grain weight by reducing the speed and period of grain filling, eventually lowering the yield. In such conditions, selecting genotypes with higher seed-filling speeds can lead to the selection of drought-tolerant genotypes. However, the speed of seed filling and the effective period of seed filling alone cannot guarantee a high yield, and other factors affecting yield should be considered in the selection of drought-tolerant genotypes.